Measuring and managing radiologist workload: Measuring radiologist reporting times using data from a Radiology Information System. Issue 5 (12th July 2013) - Cowan, Ian A; MacDonald, Sharyn LS; Floyd, Richard A
Abstract Introduction Historically, there has been no objective method of measuring the time required for radiologists to produce reports during normal work. We have created a technique for semi‐automated measurement of radiologist reporting time, and through it produced a robust set of absolute time requirements and relative value units for consultant reporting of diagnostic examinations in our hospital. Methods A large sample of reporting times, recorded automatically by the Radiology Information System (COMRAD, Software Innovations, Christchurch, New Zealand) along with the description of each examination being reported, was placed in a database. Analysis was confined to diagnostic reporting by consultant radiologists. A spreadsheet was produced, listing the total number and the frequency of reporting times of each distinct examination. Outliers with exceptionally long report times (more than 10 min for plain radiography, 30 min for ultrasound, or 60 min for CT or MRI with some exceptions) were culled; this removed 9.5% of the total. Complex CTs requiring separate workstation time were assigned times by consensus. The median time for the remainder of each sample was the assigned absolute reporting time in minutes and seconds. Relative value units were calculated using the reporting time for a single view department chest X‐ray of 1 min 38 s including verifying a report made using speech recognition software. Results A schedule of absolute and relative values, based on over 179 000 reports, forms Table 2 of this paper. Conclusions The technique provides a schedule of reporting times with reduced subjective input, which is more robust than existing systems for measuring reporting time.